“TRISNA” Conceptual Model and Spiritual Approach to Build Body Image, Self-Esteem, and Quality of Life in Cervical Cancer Patients at Dr. Moewardi Hospital, Surakarta, Indonesia - Rita Benya Adriani; Siti Handayani; Tri Prabowo (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The problems of cervical cancer patient’s psychological response to advanced cancer are acute crisis, struggle, anxiety, and sadness, which will interfere with their life, especially sexual relations with their partners. Sexual relations in the Javanese view are a noble, sacred bond and have the function to maintain harmony. The spiritual approach and